The Role of Value Congruity in Mediating the Influence of Brand Image, and Green Marketing on Purchasing Decisions - Imbayani, I Gusti Ayu; Gama, Agus Wahyudi Salasa; Ningrat, A. A. Surya Jaya (Philippine Social Science Journal, 2025)
Motivated by The Body Shop’s declining sales in the e-commerce landscape, this study utilized PLS-SEM to analyze how value congruity mediates the influence of brand image and green marketing on the purchasing decisions of Shopee users. The findings reveal that while brand image and green marketing are significant drivers, their impact is substantially amplified when consumer and brand values align. This underscores the strategic necessity for digital marketers to craft campaigns that resonate with personal values rather than relying solely on product features. Future research is recommended to extend this framework to other eco-friendly brands and employ mixed methods to further explore the psychological determinants of sustainable consumption.